Bio-based carbon nanoparticle and high-load-bearing fatigue-resistant natural rubber composite material as well as preparation method and application thereof
By adding porous structure bio-based carbon nanoparticles to natural rubber, the problem that existing reinforcement materials cannot improve the fatigue performance of natural rubber is solved, and the effect of reducing dynamic heat generation and improving service life is achieved.
Patent Information
- Application Number
- CN202510460508.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2025-07-18
AI Technical Summary
Existing rubber reinforcement materials such as carbon black or carbon nanotubes cannot effectively improve the fatigue performance of natural rubber under large load conditions, resulting in dynamic heat generation enhancement and reduced service life.
Bio-based carbon nanoparticles are used for modification and reinforcement. By preparing porous carbon nanoparticles and adding them to natural rubber, the formulation is optimized to improve the mechanical properties of the material and reduce dynamic heat generation.
It significantly improves the dynamic fatigue resistance of natural rubber, reduces dynamic heat generation, extends service life, and expands its application range.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of rubber reinforcing materials, and particularly relates to a bio-based carbon nanoparticle and high-load fatigue-resistant natural rubber composite material, a preparation method thereof, and an application thereof. Background Art
[0002] Natural rubber is a natural high-molecular compound mainly composed of polyisoprene. More than 97% of the molecular chains are cis-1,4 structures, which endow it with good elasticity and high elongation. The main chain of the natural rubber molecule is mainly composed of carbon-carbon bonds with high bond energy and has high mechanical properties. Therefore, natural rubber is widely used in vibration damping elastic elements in the fields of aviation, aerospace, etc.
[0003] Due to the viscoelastic characteristics of natural rubber materials, under periodic dynamic load conditions, natural rubber shows a phenomenon that strain lags behind stress, resulting in mechanical loss and dynamic heat generation. When natural rubber is applied to large-load vibration damping elastic elements, under periodic large-load vibration conditions, the strain of natural rubber increases, and the dynamic heat generation is significantly enhanced, causing the temperature of the natural rubber in the vibration damping elastic element to rise significantly, accelerating the thermal oxygen aging and fatigue damage of natural rubber, and leading to a significant reduction in the service life of large-load vibration damping elastic elements. To solve the above problems of natural rubber, rubber reinforcing materials can be added to natural rubber materials. However, although existing rubber reinforcing materials such as carbon black or carbon nanotubes can enhance the modulus and wear resistance of natural rubber materials, they cannot effectively improve mechanical loss and reduce the dynamic heat generation of rubber. When applied to large-load and high-load rubber materials, they still cannot effectively meet the requirements of the dynamic fatigue resistance performance of natural rubber materials.
[0004] Therefore, to improve the dynamic fatigue resistance of natural rubber, the preparation of a new type of high-reinforcing and low-hysteresis reinforcing material is an urgent problem to be solved at present. Summary of the Invention
[0005] To solve the problems existing in the prior art, the present invention provides a bio-based carbon nanoparticle and high-load fatigue-resistant natural rubber composite material. By adding bio-based carbon nanoparticles to natural rubber for modification and reinforcement, and optimizing the formula of natural rubber materials, a high-load fatigue-resistant natural rubber composite material is prepared, thereby improving the mechanical properties of natural rubber materials, reducing their loss factor and dynamic heat generation, slowing down the thermal aging fatigue process of natural rubber materials, and greatly improving the dynamic fatigue resistance performance of natural rubber materials.
[0006] One of the purposes of the present invention is to provide a bio-based carbon nanoparticle, a preparation method thereof, and an application thereof, so as to solve the technical problem that the reinforcing performance of existing rubber reinforcing materials is weak and it is difficult to effectively improve the poor fatigue performance of natural rubber materials under large-load conditions.
[0007] To achieve the above object, the present invention provides a method for preparing biobased carbon nanoparticles, comprising the following steps:
[0008] Squeezing the ink sac of cuttlefish to obtain cuttlefish ink;
[0009] Performing water washing and centrifugation on the cuttlefish ink to obtain a cuttlefish ink precipitate;
[0010] Performing deionization treatment on the cuttlefish ink precipitate to obtain a cuttlefish ink solution with metal ions removed;
[0011] Sequentially performing activation treatment and carbonization treatment on the cuttlefish ink solution with metal ions removed to obtain a carbonized product;
[0012] Performing post-treatment on the carbonized product to obtain the biobased carbon nanoparticles.
[0013] Further, performing water washing and centrifugation on the cuttlefish ink to obtain a cuttlefish ink precipitate, comprising: filtering the cuttlefish ink, adding the filtered filtrate to deionized water for soaking, then centrifuging the soaked filtrate, and repeatedly performing water washing and centrifugation several times to obtain a cuttlefish ink precipitate.
[0014] Further, performing deionization treatment on the cuttlefish ink precipitate to obtain a cuttlefish ink solution with metal ions removed, comprising:
[0015] Dispersing the cuttlefish ink precipitate into deionized water to obtain a cuttlefish ink solution;
[0016] Mixing the cuttlefish ink solution with a chelating agent and an anionic surfactant to obtain a mixed solution;
[0017] Adjusting the pH of the mixed solution and then introducing compressed air for foam separation to obtain a cuttlefish ink solution with metal ions removed.
[0018] Further, the activation treatment includes: adding an alkali to the cuttlefish ink solution with metal ions removed to adjust the pH value of the cuttlefish ink solution to 10 - 11, and activating at a temperature of 15 - 25 °C for 8 h.
[0019] Further, the carbonization treatment includes: performing centrifugal separation on the cuttlefish ink solution with metal ions removed after activation treatment to obtain a cuttlefish ink precipitate with metal ions removed;
[0020] Carbonizing the cuttlefish ink precipitate with metal ions removed at a heating rate of 20 - 30 °C / min under an inert atmosphere condition to 800 - 900 °C for 4 - 6 h, and then naturally cooling to room temperature to obtain a carbonized product.
[0021] Further, the post-treatment includes: subjecting the carbonized product to acid neutralization, followed by suction filtration and washing with clear water and then drying to obtain bio-based carbon nanoparticles.
[0022] Further, the present invention also provides a bio-based carbon nanoparticle, which is prepared by using the aforesaid preparation method of the bio-based carbon nanoparticle.
[0023] Further, the present invention also provides an application of the aforesaid bio-based carbon nanoparticle as a reinforcing material in rubber.
[0024] The second object of the present invention is to provide a high-load fatigue-resistant natural rubber composite material and a preparation method thereof, so as to solve the problem of poor fatigue performance of existing natural rubber materials under large load conditions, expand the application prospect of natural rubber materials, and enable them to be applied to large-load vibration damping elastic elements.
[0025] To achieve the above object, the present invention provides a high-load fatigue-resistant natural rubber composite material, comprising the following raw materials in parts by weight: 100 parts of natural rubber raw rubber, 4 - 10 parts of zinc oxide, 1 - 3 parts of stearic acid, 0 - 30 parts of carbon black, 10 - 40 parts of bio-based carbon nanoparticles, 1 - 4 parts of antioxidant, 5 - 10 parts of plasticizer, 1 - 4 parts of accelerator, 1 - 2.5 parts of vulcanizing agent, wherein the bio-based carbon nanoparticles are prepared by using the aforesaid preparation method of the bio-based carbon nanoparticle.
[0026] Further, the present invention also provides a preparation method of the aforesaid high-load fatigue-resistant natural rubber composite material, comprising the following steps:
[0027] Mixing natural rubber raw rubber, zinc oxide, stearic acid, carbon black, bio-based carbon nanoparticles, antioxidant and plasticizer to obtain a masterbatch;
[0028] Subjecting the masterbatch to roll covering, adding vulcanizing agent and accelerator, and after the vulcanizing agent and accelerator are mixed into the masterbatch, passing through several thin passes to obtain the high-load fatigue-resistant natural rubber composite material.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The bio-based carbon nanoparticles prepared by the present invention have the characteristics of porous structure and large specific surface area compared with carbon black and carbon nanotubes in the prior art, can greatly increase the interaction sites between natural rubber molecular chains and carbon nanoparticles, and at the same time, the bio-based carbon nanoparticles also contain active groups such as oxygen-containing groups and nitrogen-containing groups. As a modified reinforcing material for natural rubber materials, it greatly improves the mechanical properties of natural rubber materials, effectively reduces the dynamic heat generation of natural rubber, and significantly improves the dynamic fatigue performance of natural rubber materials.
[0031] 2. The bio-based carbon nanoparticles of the present invention are prepared from the squid ink discarded by squid processing factories, turning waste squid ink into a valuable resource and having good social benefits.
[0032] 3. The high-load fatigue-resistant natural rubber composite provided by the present invention uses bio-based carbon nanoparticles as a reinforcing filler, reducing the number of free chain segments and molecular chain ends in the natural rubber material. The dynamic properties of the material are manifested as increased elasticity, reduced viscosity, decreased mechanical loss caused by viscous deformation, and reduced dynamic heat generation of natural rubber, solving the problem of poor fatigue performance of existing natural rubber materials under large load conditions, expanding the application prospects of natural rubber materials, and being applicable to large-load vibration damping elastic elements. Specific Embodiments
[0033] It should be noted that, without conflict, the embodiments in this application and the features in the embodiments can be combined with each other. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each intermediate value within any stated value or stated range, as well as each smaller range between any other stated value or intermediate value within the stated range, is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded from the range. The present invention will be described in detail below with reference to the embodiments.
[0034] To achieve the above object, in the first aspect of the embodiments of the present invention, a preparation method of bio-based carbon nanoparticles is provided, including the following steps: extruding ink from the squid ink sac to obtain squid ink; performing water washing and centrifugation on the squid ink to obtain squid ink precipitate; performing de-metal ion treatment on the squid ink precipitate to obtain a squid ink aqueous solution with metal ions removed; sequentially performing activation treatment and carbonization treatment on the squid ink aqueous solution with metal ions removed to obtain a carbonized product; and performing post-treatment on the carbonized product to obtain the bio-based carbon nanoparticles.
[0035] The bio-based carbon nanoparticles of the present invention are porous amorphous carbon nanoparticles prepared by steps such as washing squid ink with water, centrifuging, removing metal ions, activating, carbonizing, and post-treating. Their diameter is 90-250 nanometers. The bio-based carbon nanoparticles prepared in the present invention have the characteristics of a porous structure and a large surface area. As a reinforcing material for natural rubber, they can greatly increase the interaction sites between natural rubber molecular chains and carbon nanoparticles, and more natural rubber molecular chain segments and molecular chain ends are adsorbed on the surface of carbon nanoparticles or embedded inside the pores of carbon nanoparticles. In addition, reactive groups such as residual oxygen-containing groups and nitrogen-containing groups in the bio-based carbon nanoparticles can react with groups such as aldehyde groups and carboxyl groups in natural rubber to form stable chemical bonding, or form strong intermolecular hydrogen bonds. Therefore, the bio-based carbon nanoparticles prepared in the present invention have a significant reinforcing effect on natural rubber as a filler for natural rubber, improving the mechanical properties and dynamic fatigue resistance of natural rubber materials.
[0036] In a preferred embodiment of the present invention, to further purify the squid ink precipitate, the squid ink is subjected to washing and centrifuging treatment to obtain a squid ink precipitate, which specifically includes: filtering the squid ink, adding deionized water to soak the filtered filtrate, and then centrifuging the soaked filtrate. After washing and centrifuging repeatedly several times, a squid ink precipitate is obtained.
[0037] First, the squid ink sac or other impurities that may remain in the squid ink can be removed by filtration. Then, by fully soaking the filtrate and washing and centrifuging repeatedly, a squid ink precipitate with high purity can be obtained. Further preferably, the addition amount of deionized water is 3-5 times the volume of the squid ink, the soaking time is 10-20 h, the centrifugation speed is 8000-10000 r / min, and the single centrifugation time is 15-20 min. The number of times of washing and centrifuging repeatedly is adjusted according to the actual situation. When the supernatant after centrifugation is clear, the sediment obtained after centrifugation is taken as the squid ink precipitate.
[0038] In a preferred embodiment of the present invention, the squid ink precipitate is subjected to metal ion removal treatment to obtain a squid ink solution with metal ions removed, which specifically includes: dispersing the squid ink precipitate into deionized water to obtain a squid ink solution; mixing the squid ink solution with a chelating agent and an anionic surfactant to obtain a mixed solution; adjusting the pH of the mixed solution and then introducing compressed air for foam separation to obtain a squid ink solution with metal ions removed.
[0039] Cuttlefish ink contains metal ions such as iron, cobalt, nickel, and copper. These metal ions can initiate an oxidation chain reaction or cause the rubber molecular chains to undergo an oxidation reaction according to the autocatalytic oxidation process. Therefore, in the present invention, a chelating agent and an anionic surfactant are mixed with the cuttlefish ink solution. Through the foam separation method, the metal ions such as iron, cobalt, nickel, and copper in the cuttlefish ink can be effectively removed without introducing other metal ions, and the oxidation breakage phenomenon of the natural rubber molecular chains caused by metal ions can be eliminated, improving the heat and oxygen aging resistance of the natural rubber material.
[0040] In a preferred embodiment of the present invention, the chelating agent is selected from free acid chelating agents. The free acid chelating agents can be selected from amino carboxylic acid chelating agents and / or hydroxy carboxylic acid chelating agents. The amino acid chelating agents can be, for example, selected from one or more of ethylenediaminetetraacetic acid, glutamic acid diacetic acid, and diethylenetriaminepentaacetic acid; the hydroxy carboxylic acid chelating agents can be, for example, selected from one or more of citric acid, gluconic acid, and malic acid.
[0041] In an alternative embodiment of the present invention, the anionic surfactant is, for example, selected from one or more of dodecylbenzenesulfonic acid, ammonium lauryl sulfate, and ammonium dodecylbenzenesulfonate to avoid introducing new metal ions. However, it should be understood that other anionic surfactants without metal ions are also acceptable and are not particularly limited.
[0042] To further optimize the effect of removing metal ions from the cuttlefish ink precipitate, in some preferred embodiments of the present invention, the volume ratio of the cuttlefish ink precipitate to deionized water is 1:20 - 25. For example, it can be selected from 1:20, 1:21, 1:22, 1:23, 1:24, 1:25. The chelating agent and the anionic surfactant are added in the form of a solution. The molar concentration of the chelating agent solution is 0.01 - 0.1 mol / L, for example, it can be selected from 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L, and 0.1 mol / L. The mass concentration of the anionic surfactant solution is 0.15 - 0.22 g / L, for example, it can be selected from 0.15 g / L, 0.16 g / L, 0.17 g / L, 0.18 g / L, 0.20 g / L, and 0.22 g / L. The pH of the mixed solution is adjusted to 4.0 - 5.5, and the foam separation time is 30 - 90 min.
[0043] In a preferred embodiment of the present invention, to further enrich the pore structure of the bio-based carbon nanoparticles, the activation treatment includes: adding an alkali to the metal ion-removed cuttlefish ink solution to adjust the pH value of the cuttlefish ink solution to 10-11, and activating it at a temperature of 15-25 °C for 8 h.
[0044] In a preferred embodiment of the present invention, the carbonization treatment includes: centrifugally separating the metal ion-removed cuttlefish ink solution after the activation treatment to obtain a metal ion-removed cuttlefish ink precipitate; heating the metal ion-removed cuttlefish ink precipitate in an inert atmosphere at a heating rate of 20-30 °C / min to 800-900 °C for carbonization for 4-6 h, and then naturally cooling it to room temperature to obtain a carbonized product.
[0045] The metal ion-removed cuttlefish ink precipitate is rapidly heated and carbonized under the protection of an inert gas, which can cause proteins, fats, etc. in the cuttlefish ink to be rapidly decomposed into small molecules and volatilize. At the same time, the rapid volatilization of small molecules has a role similar to that of a foaming agent, making the carbonized cuttlefish ink particles form a porous structure, greatly increasing the surface area of the carbon nanoparticles; in addition, at the above carbonization temperature and time, some oxygen-containing groups such as -OH and -CO- and nitrogen-containing groups such as -NH2 and -NH- still remain in the prepared carbon nano-ink particles, having high activity.
[0046] In an alternative embodiment of the present invention, the post-treatment includes: subjecting the carbonized product to acid neutralization, then filtering and washing it with clear water and drying it to obtain bio-based carbon nanoparticles. Preferably, the acid neutralization is carried out using hydrochloric acid; the drying temperature is 70-80 °C.
[0047] In the second aspect of the embodiments of the present invention, there is also provided a bio-based carbon nanoparticle prepared by the aforementioned method for preparing bio-based carbon nanoparticles.
[0048] For the reasons mentioned above, the bio-based carbon nanoparticles of the present invention have a rich porous structure and surface active groups. The bio-based carbon nanoparticles of the present invention are prepared from cuttlefish ink discarded by cuttlefish processing factories, turning waste cuttlefish ink into a valuable resource, and having good social benefits.
[0049] In the third aspect of the embodiments of the present invention, there is also provided an application of the aforementioned bio-based carbon nanoparticles as a reinforcing material in rubber.
[0050] For the reasons mentioned above, the bio-based carbon nanoparticles of the present invention have a good reinforcing effect on rubber materials, can improve the mechanical properties of rubber materials, effectively reduce the dynamic heat generation of rubber, and significantly improve the dynamic fatigue performance of rubber materials.
[0051] In the fourth aspect of the embodiments of the present invention, a high-load fatigue-resistant natural rubber composite material is further provided, which comprises the following raw materials in parts by weight: 100 parts of natural rubber raw rubber, 4-10 parts of zinc oxide, 1-3 parts of stearic acid, 0-30 parts of carbon black, 10-40 parts of bio-based carbon nanoparticles, 1-4 parts of antioxidant, 5-10 parts of plasticizer, 1-4 parts of accelerator, and 1-2.5 parts of vulcanizing agent, wherein the bio-based carbon nanoparticles are prepared by the aforementioned preparation method of bio-based carbon nanoparticles.
[0052] The high-load fatigue-resistant natural rubber composite material of the present invention is a mixture composed of natural rubber raw rubber, zinc oxide, stearic acid, optional carbon black, bio-based carbon nanoparticles, antioxidant, plasticizer, accelerator and sulfur. Bio-based carbon nanoparticles are used for modification and reinforcement. Due to the advantages of rich porous structure, large specific surface area, and the presence of active groups such as oxygen-containing groups and nitrogen-containing groups in the bio-based carbon nanoparticles, the number of free chain segments and the ends of molecular chains in the natural rubber material can be reduced. The dynamic properties of the material are manifested as increased elasticity, reduced viscosity, decreased mechanical loss caused by viscous deformation, and reduced dynamic heat generation of natural rubber, thereby significantly improving the dynamic fatigue performance of the natural rubber material. Further preferably, the weight parts of the carbon black are 10-30 parts, and the weight parts of the bio-based carbon nanoparticles are 20-40 parts.
[0053] In a preferred embodiment of the present invention, the weight-average molecular weight of the natural rubber raw rubber is 16×10 5 ~26×10 5 g / mol, the Mooney viscosity ML100℃(1+4) is 55-65, and the protein content is 1.0-3.0 wt%.
[0054] In a preferred embodiment of the present invention, the carbon black includes high-abrasion furnace black with a particle size of 300-400 nm. The high-abrasion furnace black can be selected from carbon black N330.
[0055] The antioxidant of the present invention can be selected from commercially available antioxidants commonly used in the art. However, in a preferred embodiment of the present invention, the antioxidant can include any one of N-cyclohexyl-N'-phenyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine, and 2,2,4-trimethyl-1,2-dihydroquinoline. Further preferably, the antioxidant includes any one of N-cyclohexyl-N'-phenyl-p-phenylenediamine and N-isopropyl-N'-phenyl-p-phenylenediamine and 2,2,4-trimethyl-1,2-dihydroquinoline, and the weight ratio of the two is 1:1~3:1.
[0056] The accelerator of the present invention can be selected from commercially available accelerators commonly used in the art. However, in a preferred embodiment of the present invention, the accelerator may include N-cyclohexyl-2-benzothiazole sulfenamide and tetramethylthiuram disulfide. Further preferably, the weight ratio of N-cyclohexyl-2-benzothiazole sulfenamide to tetramethylthiuram disulfide is 1:1 to 4:1. The plasticizer and vulcanizing agent of the present invention can be selected from commercially available naphthenic oil or aromatic oil plasticizers and sulfur-based vulcanizing agents commonly used in the art, without special limitation.
[0057] In the fifth aspect of the embodiments of the present invention, a method for preparing a high-load fatigue-resistant natural rubber composite is further provided, including the following steps:
[0058] Mix natural rubber raw rubber, zinc oxide, stearic acid, carbon black, bio-based carbon nanoparticles, anti-aging agent and plasticizer to obtain a mixed masterbatch;
[0059] Roll the mixed masterbatch, add a vulcanizing agent and an accelerator. After the vulcanizing agent and the accelerator are mixed into the mixed masterbatch, thin pass several times to obtain the high-load fatigue-resistant natural rubber composite.
[0060] The method for preparing the high-load fatigue-resistant natural rubber composite of the present invention is simple in operation, stable in process, convenient for industrial production, and has good economic benefits.
[0061] In some preferred embodiments of the present invention, the temperature of the mixing is 40°C to 110°C, and the time of the mixing is 8 to 25 min.
[0062] The following further describes the present application in detail with specific embodiments, and these embodiments should not be construed as limiting the scope claimed by the present application.
[0063] Examples 1 to 5 and Comparative Examples 1 to 2
[0064] Table 1 is a formulation table of the high-load fatigue-resistant natural rubber composites obtained in Examples 1 to 5 and Comparative Example 1 of the present invention, where the numbers in each formulation are parts by mass, and the weight-average molecular weight of the natural rubber raw rubber used is 16.7×10 5 g / mol, the Mooney viscosity ML100°C(1+4) is 56, and the protein content is 2.3 wt%.
[0065] The preparation method of the bio-based carbon nanoparticles used in Examples 1 to 5 of the present invention includes the following steps:
[0066] (1) Cut open the ink sac of the cuttlefish and squeeze out the ink. Filter it through a 120-mesh sieve, then add deionized water 4 times the volume of the ink and soak for 10 h. Centrifuge at a speed of 10000 r / min for 15 min, and repeat washing and centrifugation 6 times to obtain cuttlefish ink precipitate.
[0067] (2) The squid ink precipitate is dispersed in 20 times the volume ratio of deionized water, and ultrasonic dispersion is performed for 10 minutes to prepare a uniformly dispersed squid ink solution, and a 0.03 mol / L ethylenediaminetetraacetic acid solution and a 0.15 g / L dodecylbenzenesulfonic acid solution are added. After thorough mixing, the pH value of the mixed solution is adjusted to 4.5, and then injected into a foam separation tower, and compressed air is introduced from the bottom of the tower for foam separation for 60 minutes to obtain a squid ink solution with metal ions removed.
[0068] (3) NaOH was added to the above-mentioned metal ion-removed squid ink solution to make the solution pH 10, and the squid ink was activated at room temperature (25°C) for 8 hours. The squid ink precipitate was separated by centrifugation at a speed of 8000 r / min. The temperature was rapidly increased to 800°C at a heating rate of 20°C / min under inert gas protection and carbonized for 6 hours. Then, the solution was naturally cooled to room temperature to obtain a carbonized product.
[0069] (4) The carbonized product obtained in (3) is neutralized with hydrochloric acid, filtered and washed with clean water, and then dried at 75° C. to obtain bio-based carbon nanoparticles.
[0070] The preparation methods of the high load-bearing and fatigue-resistant natural rubber composite materials of Examples 1 to 5 are as follows:
[0071] (a) Ingredients: Weigh the raw materials according to the formula in Table 1 (the numbers in each formula are parts by mass);
[0072] (b) Mixing: natural rubber, zinc oxide, stearic acid, carbon black (brand N330), bio-based carbon nanoparticles, antioxidant and plasticizer (cyclohexane oil plasticizer) are sequentially put into an internal mixer for mixing, the mixing temperature is controlled to be 60° C., the internal mixing is performed for 25 min, and the mixing masterbatch is obtained; wherein the antioxidant is N-cyclohexyl-N′-phenyl-p-phenylenediamine (antioxidant 4010) and 2,2,4-trimethyl-1,2-dihydroquinoline (antioxidant RD);
[0073] (c) Adding vulcanizing agent: adjusting the roller distance and baffle of the two-roll rubber mixer so that the mixed masterbatch covers the rollers and adding the accelerator and the vulcanizing agent. After the accelerator and the vulcanizing agent are mixed, the mixer is thinly passed through 5 times to obtain a high-load-bearing and fatigue-resistant natural rubber composite material; wherein the accelerators are N-cyclohexyl-2-benzothiazole sulfonamide (accelerator CZ) and tetramethylthiuram disulfide (accelerator TMTD), and the vulcanizing agent is sulfur.
[0074] The preparation method of the high load-bearing and fatigue-resistant natural rubber composite material of Comparative Example 1 refers to that of Examples 1 to 5, except that no bio-based carbon nanoparticles are added during the preparation of the composite material.
[0075] The preparation method of the high-load fatigue-resistant natural rubber composite material of Comparative Example 2 was referred to Examples 1 to 5, except that the bio-based carbon nanoparticles added during the preparation of the composite material were not treated for removing metal ions. The specific preparation process of the bio-based carbon nanoparticles of Comparative Example 2 was as follows:
[0076] (1) Cut open the ink sac of the cuttlefish and squeeze out the ink. Filter it through a 120-mesh sieve, then add deionized water four times the volume of the ink and soak for 10 h. Centrifuge at a speed of 10,000 r / min for 15 min, and repeat the water washing and centrifugation six times to obtain cuttlefish ink precipitate.
[0077] (2) Take the above cuttlefish ink precipitate and disperse it in deionized water with a volume ratio of 20 times, and perform ultrasonic dispersion for 10 min to prepare a uniformly dispersed cuttlefish ink solution.
[0078] (3) Add NaOH to the above cuttlefish ink solution to make the pH value of the solution 10, activate the cuttlefish ink at room temperature (25 °C) for 8 h, centrifuge and separate at a speed of 8,000 r / min to obtain cuttlefish ink precipitate. Under the protection of inert gas, rapidly heat up to 800 °C at a heating rate of 20 °C / min and carbonize for 6 h, and then naturally cool to room temperature to obtain a carbonized product.
[0079] (4) Neutralize the carbonized product obtained in (3) with hydrochloric acid, filter and wash it with clear water, and dry it at 75 °C to obtain bio-based carbon nanoparticles.
[0080] The high-load fatigue-resistant natural rubber composite materials of Examples 1 to 5 and Comparative Examples 1 to 2 were vulcanized at 150 °C for 20 min to obtain high-load fatigue-resistant natural rubber composite material specimens. The obtained high-load fatigue-resistant natural rubber composite material specimens were subjected to the following performance tests, and the performance test results are shown in Table 2.
[0081] The hardness test was carried out in accordance with GB / T 531.1-2008 "Vulcanized Rubber or Thermoplastic Rubber - Indentation Hardness Test Method - Part 1: Shore Hardness".
[0082] The tensile strength and 100% modulus at 100% elongation tests were carried out in accordance with GB / T 528-2009 "Vulcanized Rubber or Thermoplastic Rubber - Determination of Tensile Stress-Strain Properties".
[0083] The tear strength test was carried out in accordance with GB / T 529-2008 "Vulcanized Rubber or Thermoplastic Rubber - Determination of Tear Strength (Trouser, Right Angle and Crescent Specimens)".
[0084] The heat build-up in compression test was carried out in accordance with GB / T 1687-1993 "Vulcanized Rubber - Determination of Temperature Rise and Fatigue Resistance in Flexing".
[0085] The fatigue cycle test was carried out on an electro-hydraulic servo testing machine. The test conditions were pre-compression of 5%, dynamic amplitude of 15%, frequency of 10 Hz. The compression stiffness at 5 minutes of the test time was taken as the initial compression stiffness, and the number of compression cycles when the compression stiffness of the specimen decreased by 20% was taken as the fatigue life.
[0086] Table 1 Formulation table of high-load fatigue-resistant natural rubber composites for Examples 1 - 5 and Comparative Examples 1 - 2
[0087]
[0088] Table 2 Performance test table of high-load fatigue-resistant natural rubber composites for Examples 1 - 5 and Comparative Examples 1 - 2
[0089]
[0090] For the natural rubber composites of Examples 1 - 4 in Table 1, carbon black and bio-based carbon nanoparticles were used as reinforcing materials. For Example 5, bio-based carbon nanoparticles were used alone as the reinforcing material. For Comparative Example 1, the natural rubber composite only used carbon black as the reinforcing filler, while for Comparative Example 2, bio-based carbon nanoparticles and carbon black were used as the reinforcing materials, but the metal ion removal treatment was not carried out during the preparation of the bio-based carbon nanoparticles.
[0091] The results in Table 2 show that compared with Comparative Example 1, the mechanical properties such as hardness, tensile strength, 100% modulus at elongation, tear strength and fatigue properties of the natural rubber composites prepared in Examples 1 - 5 of the present invention have been improved to varying degrees, and the temperature of compression heat generation has been significantly reduced, indicating that the bio-based carbon nanoparticles of the present invention have a good reinforcing effect on natural rubber as a reinforcing filler, improving the mechanical properties and dynamic fatigue resistance of natural rubber materials.
[0092] The test results of Comparative Examples 1 - 2 and Example 1 show that both the bio-based carbon nanoparticles prepared with and without metal ion removal can improve the mechanical properties of natural rubber, but the fatigue resistance of natural rubber using bio-based carbon nanoparticles without metal ion removal is significantly reduced, while the fatigue resistance of natural rubber using bio-based carbon nanoparticles with metal ion removal is significantly improved. It is proved that the treatment of removing metal ions can effectively remove metal ions such as iron, cobalt, nickel, copper, etc. in bio-based carbon nanoparticles, eliminate the oxidation and fracture phenomenon of natural rubber molecular chains caused by metal ions, and significantly improve the fatigue resistance of natural rubber.
[0093] Examples 6 - 10 and Comparative Examples 3 - 4
[0094] Table 3 is a formula table of high load-bearing and fatigue-resistant natural rubber composite materials obtained in Examples 6 to 10 of the present invention and Comparative Examples 3 to 4, wherein the numbers in each formula are weight parts, and the weight average molecular weight of the natural rubber raw rubber used is 25.3×10 5 g / mol, Mooney viscosity ML100℃(1+4) is 63, and protein content is 2.6wt%.
[0095] The method for preparing the bio-based carbon nanoparticles used in Examples 6 to 10 of the present invention comprises the following steps:
[0096] (1) Cut the cuttlefish ink sac to squeeze out the ink, filter it through a 120-mesh sieve, and then add deionized water 5 times the volume of the ink to soak for 20 hours. Centrifuge it at a speed of 8000 r / min for 20 minutes, and repeat the water washing and centrifugation for 6 times to obtain the cuttlefish ink precipitate.
[0097] (2) The squid ink precipitate was dispersed in 25 times the volume ratio of deionized water, and ultrasonic dispersion was performed for 8 minutes to prepare a uniformly dispersed squid ink solution, and a 0.03 mol / L ethylenediaminetetraacetic acid solution and a 0.22 g / L dodecylbenzenesulfonic acid solution were added. After thorough mixing, the pH value of the mixed solution was adjusted to 5.3, and then injected into a foam separation tower, and compressed air was introduced from the bottom of the tower for foam separation for 60 minutes to obtain a squid ink solution with metal ions removed.
[0098] (3) NaOH was added to the above-mentioned metal ion-removed squid ink solution to make the solution pH 11, and the squid ink was activated at room temperature (25°C) for 8 hours. The squid ink precipitate was separated by centrifugation at a speed of 8000 r / min. The temperature was rapidly increased to 900°C at a heating rate of 30°C / min under inert gas protection and carbonized for 4 hours. Then, the solution was naturally cooled to room temperature to obtain a carbonized product.
[0099] (4) The carbonized product obtained in (3) is neutralized with hydrochloric acid, filtered and washed with clean water, and then dried at 80° C. to obtain bio-based carbon nanoparticles.
[0100] The preparation methods of the high load-bearing and fatigue-resistant natural rubber composite materials of Examples 6 to 10 are as follows:
[0101] (a) Ingredients: Weigh the raw materials according to the formula in Table 3 (the numbers in each formula are parts by mass);
[0102] (b) Mixing: Raw natural rubber, zinc oxide, stearic acid, carbon black (grade N330), bio-based carbon nanoparticles, antioxidant, and plasticizer were sequentially fed into a Banbury mixer for mixing. The mixing temperature was controlled at 90 °C, and after mixing for 15 min, the discharge was obtained to get the masterbatch; among them, the antioxidant was N-isopropyl-N'-phenyl-p-phenylenediamine (antioxidant 4010NA) and 2,2,4-trimethyl-1,2-dihydroquinoline (antioxidant RD).
[0103] (c) Adding vulcanizing agent: Adjust the roll gap and baffle of the two-roll rubber mill to make the masterbatch wrap around the roll and add accelerator and sulfur. After the accelerator and vulcanizing agent were mixed, it was passed through the mill 5 times thinly to obtain a high-load fatigue-resistant natural rubber composite material. Among them, the accelerator was N-cyclohexyl-2-benzothiazole sulfenamide (accelerator CZ) and tetramethylthiuram disulfide (accelerator TMTD), and the vulcanizing agent was sulfur. The high-load fatigue-resistant natural rubber composite material was vulcanized at 150 °C for 15 min to obtain the high-load fatigue-resistant natural rubber composite material.
[0104] The preparation method of the high-load fatigue-resistant natural rubber composite material of Comparative Example 3 was referred to Examples 6 to 10, except that bio-based carbon nanoparticles were not added during the preparation process of this composite material.
[0105] The preparation method of the high-load fatigue-resistant natural rubber composite material of Comparative Example 4 was referred to Examples 6 to 10, except that the bio-based carbon nanoparticles added during the preparation process of this composite material were not treated for removing metal ions. The preparation process of the bio-based carbon nanoparticles of Comparative Example 4 was specifically as follows:
[0106] (1) Cut open the ink sac of the cuttlefish and squeeze out the ink. Filter it through a 120-mesh sieve, then add deionized water 5 times the volume of the ink and soak for 20 h. Centrifuge at a speed of 8000 r / min for 20 min, and repeat the washing and centrifugation 6 times to obtain cuttlefish ink precipitate.
[0107] (2) Take the above cuttlefish ink precipitate and disperse it in deionized water with a volume ratio of 25 times, and perform ultrasonic dispersion for 8 min to prepare a uniformly dispersed cuttlefish ink solution.
[0108] (3) Add NaOH to the above cuttlefish ink solution to make the pH value of the solution 11, activate the cuttlefish ink at room temperature (25 °C) for 8 h, centrifuge and separate at a speed of 8000 r / min to obtain cuttlefish ink precipitate. Under the protection of inert gas, rapidly heat up to 900 °C at a heating rate of 30 °C / min and carbonize for 4 h, then naturally cool to room temperature to obtain a carbonized product.
[0109] (4) Neutralize the carbonized product obtained in (3) with hydrochloric acid, filter and wash it with clear water, and dry it at 80 °C to obtain bio-based carbon nanoparticles.
[0110] The high load-bearing and fatigue-resistant natural rubber composites of Examples 6 to 10 and Comparative Examples 3 to 4 were vulcanized at 150 °C for 20 min to obtain specimens of high load-bearing and fatigue-resistant natural rubber composites. The obtained specimens of high load-bearing and fatigue-resistant natural rubber composites were subjected to the following property tests, and the test results are shown in Table 4.
[0111] The hardness test was carried out in accordance with GB / T 531.1-2008 "Vulcanized Rubber or Thermoplastic Rubber - Determination of Indentation Hardness - Part 1: Shore Hardness".
[0112] The tensile strength and 100% modulus at 100% elongation tests were carried out in accordance with GB / T 528-2009 "Vulcanized Rubber or Thermoplastic Rubber - Determination of Tensile Stress-Strain Properties".
[0113] The tear strength test was carried out in accordance with GB / T 529-2008 "Vulcanized Rubber or Thermoplastic Rubber - Determination of Tear Strength (Trouser, Right Angle and Crescent Specimens)".
[0114] The heat build-up in compression test was carried out in accordance with GB / T 1687-1993 "Vulcanized Rubber - Determination of Temperature Rise and Resistance to Fatigue in Flexing".
[0115] The fatigue times were tested on an electro-hydraulic servo testing machine. The test conditions were a pre-compression of 5%, a dynamic amplitude of 15%, a frequency of 10 Hz. The compression stiffness at 5 min of the test time was taken as the initial compression stiffness, and the number of compressions when the compression stiffness of the specimen decreased by 20% was taken as the fatigue times.
[0116] Table 3 Formulation of High Load-bearing and Fatigue-resistant Natural Rubber Composites of Examples 6 to 10 and Comparative Examples 3 to 4
[0117]
[0118] Table 4 Property Test Table of High Load-bearing and Fatigue-resistant Natural Rubber Composites of Examples 6 to 10 and Comparative Examples 3 to 4
[0119]
[0120] The preparation process parameters of the bio-based carbon nanoparticles in Table 3 are different from those in Table 1. The test results of Comparative Example 3 and Examples 6 to 10 in Table 4 show that within the defined range of the present invention, using bio-based carbon nanoparticles prepared with process parameters different from those of Example 1 as the reinforcing material can also improve the mechanical properties such as the hardness, tensile strength, 100% modulus at 100% elongation, and tear strength of natural rubber vulcanizates and the fatigue performance, which is beneficial to improving the load-bearing capacity of natural rubber; at the same time, the heat build-up in compression of the natural rubber composite is reduced, and the dynamic fatigue temperature rise is decreased, which can effectively slow down the thermal aging process during the fatigue of natural rubber and improve the fatigue resistance of natural rubber.
[0121] The test results of Comparative Examples 3-4 and Example 6 show that the mechanical properties and compression heat generation properties of natural rubber reinforced with bio-based carbon nanoparticles with and without metal ions removed are comparable. However, the fatigue resistance of natural rubber reinforced with bio-based carbon nanoparticles without metal ions removed is significantly deteriorated, while the fatigue resistance of natural rubber reinforced with bio-based carbon nanoparticles with metal ions removed is significantly improved. Therefore, when preparing bio-based carbon nanoparticles for high-load and fatigue-resistant natural rubber, the treatment of removing metal ions must be carried out.
[0122] Obviously, the above-mentioned embodiments of the present invention are only examples for clearly illustrating the present invention, rather than limitations on the implementation manners of the present invention. For those of ordinary skill in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to enumerate all the implementation manners here. Any obvious changes or modifications derived from the technical solutions of the present invention still fall within the protection scope of the present invention.
Claims
1. A preparation method of biobased carbon nanoparticles, characterized in that, It includes the following steps: Squeeze the ink sac of the cuttlefish to obtain cuttlefish ink; Perform water washing and centrifugation on the cuttlefish ink to obtain cuttlefish ink precipitate; Perform de-metal ion treatment on the cuttlefish ink precipitate to obtain a cuttlefish ink solution with metal ions removed; Perform activation treatment and carbonization treatment on the cuttlefish ink solution with metal ions removed in sequence to obtain a carbonized product; Perform post-treatment on the carbonized product to obtain the bio-based carbon nanoparticles; 2. The preparation method of the bio-based carbon nanoparticles according to claim 1, wherein Performing water washing and centrifugation on the cuttlefish ink to obtain cuttlefish ink precipitate includes: Filter the cuttlefish ink, add the filtered filtrate to deionized water for soaking, and then centrifuge the soaked filtrate. After repeatedly washing and centrifuging several times, cuttlefish ink precipitate is obtained; 3. The preparation method of the bio-based carbon nanoparticles according to claim 1, wherein, Performing de-metal ion treatment on the cuttlefish ink precipitate to obtain a cuttlefish ink solution with metal ions removed includes: Disperse the cuttlefish ink precipitate into deionized water to obtain a cuttlefish ink solution; Mix the cuttlefish ink solution with a chelating agent and an anionic surfactant to obtain a mixed solution; Adjust the pH of the mixed solution and then introduce compressed air for foam separation to obtain a cuttlefish ink solution with metal ions removed; 4. The preparation method of the bio-based carbon nanoparticles according to claim 1, wherein, The activation treatment includes: adding an alkali to the cuttlefish ink solution with metal ions removed to adjust the pH value of the cuttlefish ink solution to 10-11, and activating at a temperature of 15-25°C for 8 hours; 5. The preparation method of the bio-based carbon nanoparticles according to claim 1, wherein, The carbonization treatment includes: Centrifuge and separate the cuttlefish ink solution with metal ions removed after activation treatment to obtain a cuttlefish ink precipitate with metal ions removed; Heat the cuttlefish ink precipitate with metal ions removed under an inert atmosphere condition at a heating rate of 20-30°C / min to 800-900°C for carbonization for 4-6 hours, and then naturally cool to room temperature to obtain a carbonized product; 6. The preparation method of the bio-based carbon nanoparticles according to claim 1, wherein The post-treatment includes: performing acid neutralization on the carbonized product, and then filtering and washing with clear water and drying to obtain bio-based carbon nanoparticles; 7. A bio-based carbon nanoparticle, characterized in that, It is prepared by using the preparation method of the bio-based carbon nanoparticles according to any one of claims 1 to 6; 8. Application of the bio-based carbon nanoparticles according to claim 7 as a reinforcing material in rubber; 9. A high-load-bearing and fatigue-resistant natural rubber composite material, characterized in that, It includes the following raw materials in parts by weight: 100 parts of natural rubber raw rubber, 4-10 parts of zinc oxide, 1-3 parts of stearic acid, 0-30 parts of carbon black, 10-40 parts of bio-based carbon nanoparticles, 1-4 parts of antioxidant, 5-10 parts of plasticizer, 1-4 parts of accelerator, 1-2.5 parts of vulcanizing agent, wherein the bio-based carbon nanoparticles are prepared by using the preparation method of the bio-based carbon nanoparticles according to any one of claims 1 to 6; 10. A preparation method of the high-load fatigue-resistant natural rubber composite material as described in claim 9, characterized in that, It includes the following steps: Mix natural rubber raw rubber, zinc oxide, stearic acid, carbon black, bio-based carbon nanoparticles, antioxidant and plasticizer to obtain a mixed masterbatch; Perform roll covering on the mixed masterbatch, add a vulcanizing agent and an accelerator, and after the vulcanizing agent and the accelerator are mixed into the mixed masterbatch, thin pass several times to obtain the high-load fatigue-resistant natural rubber composite material.